Obstacles in The Implementation of Sayang Bunda E-Health Application - Ambar Dwi Erawati; Chusnul Zulaika; Mona Tiorina Manurung (Universitas Ahmad Dahlan, 2021)
Background: The Sayang Bunda application is an E-Health android application offered by the Semarang City Health Office which provides consultation services to pregnant women and postpartum mothers. E-Health is considered effective as a medium for consulting pregnant women in the city of Semarang. However, based on a preliminary survey to pregnant women, there are pregnant women who do not use and even do not know the application. The purpose of this study was to explore the obstacles in the implementation of the